2016
DOI: 10.1556/036.103.2016.2.3
|View full text |Cite
|
Sign up to set email alerts
|

Protective effects of Vitamin E on CCl4-induced testicular toxicity in male rats

Abstract: The increased generation of free radicals plays an important role in testicular damage. The present study aimed to investigate the adverse effects of carbon tetrachloride (CCl 4 ) on the reproductive system of male rats as well as to examine whether Vitamin E (VE) is able to ameliorate these effects. The rats were equally divided into three groups: control, CCl 4 -treated, and CCl 4 + VE-treated groups. After 4 weeks of treatment, the decrease in body and testes weights, sperm parameters, and the decrease in s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
2
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 36 publications
4
2
0
1
Order By: Relevance
“…The significant reduction in body weight may be due to a decrease in food intake, which leads to a decrease in the body weight of the CCl4-treated group. The results of the current study were compatible with other studies [12,[21][22][23] which elucidated that CCl4 compounds caused a decline in the body weight of treated animals compared to the control.…”
Section: Discussionsupporting
confidence: 92%
“…The significant reduction in body weight may be due to a decrease in food intake, which leads to a decrease in the body weight of the CCl4-treated group. The results of the current study were compatible with other studies [12,[21][22][23] which elucidated that CCl4 compounds caused a decline in the body weight of treated animals compared to the control.…”
Section: Discussionsupporting
confidence: 92%
“…The interstitial spaces also showed acidophilic exudates and congested blood vessels. Similar observations were reported by El-Faras et al [52] who found a marked degeneration of the spermatogenic layers and interlobular hemorrhage. Al-Olayan et al [48] reported a prominent inflammation, complete swallowing of seminiferous tubules and degenerated germ cells in the testis or rats treated with CCl 4 .…”
Section: Tablesupporting
confidence: 90%
“…Actually, the decrease of antioxidant enzymes in the testicular tissue in CCl 4 -treated animals was reported previously [48] and indicated the decrease in the bioavailability of GSH due to the enhancement of lipid peroxidation and/or the inactivation of the antioxidant enzymes during oxidative stress and the accumulation of superoxide anion O 2 [49]. CCl 4 induced a significant decrease in serum testosterone level, which may be directly through the degeneration of Leydig cells due to the excessive oxidative stress [48] or indirectly through the stimulation of P450, which catalyses the production of estrogen from androgen [50,51] as was reported by several authors [52,53].…”
Section: Tablementioning
confidence: 72%
“…Vitamin E'nin bu koruyucu etkisinin, serbest radikalleri dog rudan su pu ru cu o zellig inden kaynaklanıyor olabileceg i ileri su ru lmu ştu r (30). Yapılan bir çalışmada Karbon tetrakloru r ve Vitamin E uygulanan sıçanların vu cut ve testis ag ırlıg ının kontrol grubu du zeyine çekildig i bildirilmiştir (31). Sodyum arsenit uygulamasına maruz kalan sıçanların testis dokusunda oluşan hasara karşı Vitamin E'nin seminifertu bu l çapını arttırarak, seminifertu bu l duvarını kalınlaştırarak ve tu bu l lu menindeki boşlug u azaltarak testislerin morfolojik go ru numu nde du zeltici etki sag ladıg ı go ru lmu ştu r (32) (31), dig er bir çalışmada ise Vitamin E'nin dioksinle oluşturulan testis hasarını du şu rdu g u ve azalan sperm sayısı, testosteron, LH ve FSH seviyelerini antagonize ettig i go sterilmiştir (33).…”
Section: Tartişma Ve Sonuçunclassified